BIOTEST TO THE EFFECTIVENESS OF UREA IN DEGRADATION AFLATOXIN B1 IN SUNFLOWER MEAL - Alsaidy, Hadi A.; Sameer, Salah H. (Diyala Agricultural Sciences Journal, 2015)
This study was conducted in the Department of Plant Protection - College of Agriculture - University of Baghdad in order to evaluate the effectiveness of urea in degradation aflatoxin B1 in sunflower meal bio‐available on broiler chickens type Fabro – CD. The Urea in concentration 5% caused the complete inhibition of the growth of fungus A. flavus and production of aflatoxin B1 and degradation it in sunflower meal. Results of bioassay proved that the presence of aflatoxin B1 at concentration 4.7 µg/g in sunflower meal in feed of chicken at one day age until 21 days caused significant reduction in chicken weight 12333, 286.67, and 360.0 gm and increased mortality 27% compared to the control treatment 186.67, 833.33 and 1066.67 gm and 0.0 respectively and weight of liver and spleen and gizzard 4.08, 0.19 and 8.96 gm/100gm compared to the control treatment 3.84,0.08and 6.53 gm/100gm and significant reduction in bursal fabricious weight and body weight 0.11 and 114.2 gm/100gm compared to the control treatment 0.16 and 270.4 gm/100 gm respectively. However , there was no significant difference in heart weight 0.90 compared to the control treatment 0.93.More ever , results showed that aflatoxin B1 caused significant reduction in blood characters , hemoglobin and number of red blood count RBC 5.29 gm/100gm and 1.81x10⁶ cell/ml³ measurement to the control treatment 8.78 gm/100gm and 2.39х10⁶ cell/ml³. However aflatoxin B1 achieved increase in number of white blood cell count WBC 22.96х10³ cell/ml³ and heterophills to lymphocytes ratio H : L was 0.47 measurement to the control treatment 19.48х10³ cell/ml³ and 0.24. Also , aflatoxin B1 changed the biochemical characteristics of blood , reduction in total protein , glucose and cholesterol 4.33, 1660.0 and 182.7 µg/100 ml and increased uric acid 9.67 gm/100ml compared to the control treatment 5.73, 176.7 and 192.7 µg/100 ml and 4.27 gm/100ml respectively with reduction of albumins (Pre-alb. , albumin , Postalb.) 1.61,17.43and 16.43% and globulins ( α , β , and γ globulin ) 13.66, 7.64 and 19.57% and transferrine 8.26% compared to the control treatment 2.51, 24.88 and 20.73% and 15.26, 11.55 and 25.65% and 10.11% respectively. As well as reduce the effectiveness of the enzymes GOT, GPT and ALP 67.3, 4.5 and 25.4 IU/ml compared to the control treatment 104.3, 9.8 and 32.4 IU/ml. Aflatoxin B1 reduced significantly moister and protein of liver 70.32 and 15.66% compared to control 77.00 and 17.76% and increased lipid ratio 11.78% with no difference in ratio of carbohydrates and ash 1.03 and 1.21% compared to the control treatment 5.98, 1.04 and 1.22% respectively. The urea 5% showed a significant improvement in the all studied characters and reduce the negative effect of aflatoxin B1 in broiler chickens.